Qualitative Study of the Causes and Backgrounds of High School Violence among Adolescents - Mehran Sohrabzadeh; Mohamad Solimannjad (توسعه اجتماعی, 2020)
In recent years, the phenomenon of violence among adolescents has become a major concern for sociologists, families, and education experts. This study aims to provide a qualitative study of the phenomenon of violence among high school adolescents in order to provide a clear understanding of the causes and grounds for violence and its spread at the school level. Theoretical considerations of the research have been developed based on the views of sociologists and theories related to social harms. This research has been done by qualitative method and grand theory approach. The sampling method was purposeful with a theoretical sampling strategy and the data collection method was a semi-structured in-depth interview with 17 students studying in high schools and vocational schools in Dehloran. The findings consist of 37 conceptual codes and 8 main categories including social bullying, resistance and disobedience, physical self-harm, decreased level of social resilience, conflicting speech, sexual desire and alteration, stress and the possibility of family breakdown and inflammatory outbursts of anger. "Forms of Representation of Violence" are named after the categories.